Effect of the cavity disinfectant containing chitosan on dentin bonding strength after radiotherapy - Derya Gursel Surmelioglu; Ayşenur Gungor Borsoken; Gorkem Kervancıoglu; N Ezgi Yeniceri Hilaloglu (Journal of Infection in Developing Countries)
Introduction: This study aimed to compare the bond strength of teeth treated with radiotherapy with two cavity disinfectants (Chlorhexidine gluconate, a chitosan-containing agent).